Thomas Feichtner design unplugged : sketches = skizzen - Herausgegeben von; Mit Beitragen von; Christoph Thun-Hohenstein; Gunter Schonberger; Michael Hausenlas (Basel, Switzerland Birkhäuser Verlag, 2016)
The over 200 pencil sketches in Thomas Feichtner-Design Unplugged afford unadulterated insights into the daily work of an established Austrian product designer. They show how sketches done by hand function as a central element in Feichtner's design process, and they also serve to visually encapsulate his creative output: designs born not out of the full orchestration of all available digital tools, but rather "unplugged" --reduced to pencil and paper. With a comprehensive catalog of works and written contributions by Christoph Thun-Hohenstein, Gunter Schonberger, and Michael Hausenblas." -- Provided by publisher
Includes bibliographic references (page190).
Keywords: Feichtner, Thomas, 1970 -- Notebooks, sketchbooks, etc; Design; Furniture design; Industrial design